2010
DOI: 10.1093/annonc/mdp267
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes after conservative treatment of advanced-stage serous borderline tumors of the ovary

Abstract: This study demonstrates that spontaneous pregnancies can be achieved after conservative treatment of advanced-stage borderline ovarian tumors (with noninvasive implants) but the recurrence rate is high. Nevertheless, this high rate has no impact on survival. Conservative surgery can be proposed to patients with a borderline tumor of the ovary and noninvasive peritoneal implants. Should infertility persist following treatment of the borderline tumor, an in vitro fertilization procedure can be cautiously propose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
81
1
5

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(90 citation statements)
references
References 28 publications
3
81
1
5
Order By: Relevance
“…The studies included 2624 patients with serous borderline ovarian tumour (sBOT), 2120 patients with mucinous borderline ovarian tumour (mBOT) 165 other types of BOT (endometrioid, mixed, clear cell tumours and unspecified subtypes, ( Table 2). Of these studies, seven included only patients with sBOT [1,7,10,11] (four of which included only late-stage sBOT [12][13][14][15]), and two included only mBOT [16,17]. Regarding the presence of implants, 18 studies mentioned the presence and type of implants, while three mentioned only the presence of implants.…”
Section: Participant Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…The studies included 2624 patients with serous borderline ovarian tumour (sBOT), 2120 patients with mucinous borderline ovarian tumour (mBOT) 165 other types of BOT (endometrioid, mixed, clear cell tumours and unspecified subtypes, ( Table 2). Of these studies, seven included only patients with sBOT [1,7,10,11] (four of which included only late-stage sBOT [12][13][14][15]), and two included only mBOT [16,17]. Regarding the presence of implants, 18 studies mentioned the presence and type of implants, while three mentioned only the presence of implants.…”
Section: Participant Characteristicsmentioning
confidence: 99%
“…Considering the studies that included only sBOT patients and those studies where recurrence data were provided according to histological subtypes, a total of 433 sBOT patients, enclosing 10 studies [3,[11][12][13][14][15][21][22][23][24], were analysed. The recurrence rate for C, USO and USO + CC were respectively 43.2% (95% CI = 0.349-0.519), 32.1% (95% CI = 0.251-0.400) and 15.3% (95% CI = 0.064-0.320).…”
Section: Sub-analysis For Sbotmentioning
confidence: 99%
“…Data from the recent literature are reassuring regarding the efficacy and safety of conservative surgery (i.e., involving the preservation of the uterus and at least part of one ovary, with comprehensive surgical staging) for borderline tumors of the ovary in all stages [68,70,110]. When conservative management is not feasible because of massive bilateral ovarian tumor involvement, at least the uterus can be preserved for eventual transfer of frozen embryos obtained before radical surgery.…”
Section: Conservative Surgerymentioning
confidence: 99%
“…Uzan found that histological items, such as type of pathology (serous or mucinous), papillary projection, and micro invasion, were not associated with recurrence rate of BOT (16). However, in another study, it was shown that the mucinous type caused higher recurrence rate and shorter interval between diagnosis and relapse (17).…”
Section: Discussionmentioning
confidence: 96%